Stamps on Mica-dusted Ware - Deru, Xavier; Liesen, Bernd; Daszkiewicz, Małgorzata; Schneider, Gerwulf (Rei Cretariae Romanae Fautorum Acta, 2022)
A small number of stamps on Mica-dusted Ware were recorded from Gallia Belgica, Germania superior, Germania inferior and Britannia. Both anepigraphic stamps and name stamps appear on a small range of beakers, bowls and dishes. Certain fabrics and chemical groups were distinguished, but only one workshop producing stamped vessels is known. The majority of the stamped vessels were in use from Flavian times to the early 2nd century. Some of the workshops were involved in organized long distance trade, while others only supplied locally.